Computational study of cobalt oxide: Nanoparticles, surfaces and thin films supported on metal oxide surfaces / Ala’ Omar Hasan Zayed - Ala’ Omar , Hasan Zayed (2018)
In this study, investigation of the structural, energetic, electronic, and magnetic properties of several forms of cobalt oxides as clusters, films and surfaces had been carried out. Besides using our genetic algorithm code called Universal Genetic Algorithm (UGA) combined with DFT calculations to find the global and local energy minimum structures of (CoO)n (n = 3 − 7) clusters, we have also extended the search space to (CoO)nq (n = 3−10, q = 0, +1) clusters by another code of ours, the Modified Basin-Hopping Monte Carlo Algorithm (MBHMC) program, accompanied by accurate DFT calculations. Analysis of the stability of these global minima structures are not just supported by the results of binding energies, second-order total energy difference, chemical hardness, chemical potential and HOMO-LUMO gaps, but also confirmed by the dissociation patterns of (CoO)nq clusters that fit well with available experimental data. In addition, we also explored the electronic and magnetic behavior of the clusters to understand the reasons behind the remarkable stability of certain sizes of (CoO)n systems observed in previous experimental and computational studies. The growth mechanism of cobalt oxide (II) on the magnesia surface using the DFT+U calculations was also carried out. As the first steps in understanding the growth of the CoO film, we also addressed the diffusion and adsorption behavior of cobalt atom and cobalt oxide (II) molecule on the MgO(100) surface. Furthermore, the density of state and charge transfer calculations of CoO adsorption on the MgO(100) surface and the effect of the non-polar MgO(100) surface on the magnetic characteristic of the CoO layer had also been studied. Finally, results on the different properties of the Co3O4(100) surface are also presented.